Connotation, Structure and Optimization Strategy of Teaching Sensitivity - Yuru Chen (Journal on Education, 2022)
Teachers' teaching sensitivity is a process of being direct and sensitive to educational phenomena in specific teaching situations, grasping the opportunity of education and responding in time. Teaching sensitivity occurs in specific educational situations. Teachers' sensitivity to educational resources, educational objects, etc. lies in teachers' teaching wit and educational wisdom in applying professional knowledge and theory. Its composition is obviously complicated. As far as the content dimension is concerned, teaching sensitivity can be divided into different contents and categories, including moral sensitivity, emotional sensitivity, cultural sensitivity and action sensitivity. Teachers' sensitivity optimization strategies explore more appropriate training methods from different dimensions. This research method was used in this research is a qualitative study of library research that focuses on books and other documents. a type of research used was qualitative. The cultivation of teachers' educational sensitivity will prompt them to constantly check, examine and demonstrate the logic, rationality, and educational nature of educational behavior in their own educational and teaching practice. Once teachers' educational ideals and values are examined and confirmed in real life, the essential significance of education and teachers' value pursuit can be built on a more solid foundation, and the significance of education and teachers' personal values can be realized. While having teaching sensitivity, teachers should also focus on improving their "wisdom" aspects in teaching, so that they can have both "wisdom" and "wisdom" in teaching life. It is not a simple matter of a day or two to improve teachers' teaching and practical wisdom. Teachers need to break free from the shackles of old and old teaching habits, and on the basis of maintaining a high degree of sensitivity, turn knowledge into wisdom, and express the essence of their teaching work in a professional and practical form.